2010
DOI: 10.1086/655821
|View full text |Cite
|
Sign up to set email alerts
|

Does Food Insecurity Affect Parental Characteristics and Child Behavior? Testing Mediation Effects

Abstract: Using two waves of data from the Child Development Supplement in the Panel Study of Income Dynamics, this study investigates whether parental characteristics (parenting stress, parental warmth, psychological distress, and parent’s self-esteem) mediate household food insecurity’s relations with child behavior problems. Fixed-effects analyses examine data from a low-income sample of 416 children from 249 households. This study finds that parenting stress mediates the effects of food insecurity on child behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 31 publications
3
100
1
2
Order By: Relevance
“…Moreover, studies have shown that nutritional deficiencies can lead to periodontal disease [11], which is another determinant of tooth loss.…”
Section: Brazilian Research In Pediatric Dentistry and Integrated CLImentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have shown that nutritional deficiencies can lead to periodontal disease [11], which is another determinant of tooth loss.…”
Section: Brazilian Research In Pediatric Dentistry and Integrated CLImentioning
confidence: 99%
“…Studies have shown that adults in situations of FI are more susceptible to heart disease, diabetes, hypertension, increased inflammation [7] and obesity [8]. Moreover, children in families experiencing FI are more prone to psychosocial [9], cognitive [10] and behavioral [11] problems as well as stomachache, headache [12], asthma [13), a reduction in the intake of important nutrients [14] and developmental deficiencies [15].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of life caused by hunger is dwarfed by the invisible and permanent loss of human potential. Lack of food raises healthcare costs and reduces workforce productivity (Shepard et (Howard, 2011), lower nutrient intakes (Cook et al, 2004), dysthymia and other mental health issues (Alaimo et al, 2002), asthma (Kirkpatrick et al, 2007), behavioral problems (Huang et al, 2010), depression (Whitaker et al, 2006), diabetes (Seligman et al, 2007) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Because parenting characteristics are correlated with food insecurity and child behaviour problems (14) , the study controlled for parenting stress and maternal depression. Parenting stress was measured using an average of responses to four questions such as 'Being a parent is harder than I thought it would be'.…”
Section: Child Sleep Patternsmentioning
confidence: 99%
“…Low-income households have lower access to supermarkets and are left with convenience stores that provide mostly foods of little nutritional value (25) . Given that food insecurity also contributes to child behaviour problems (14)(15)(16)(17) , there may be a differential relationship between soft drinks consumption and child behaviour problems by food security status.…”
mentioning
confidence: 99%